Association of rheumatic diseases with symptom severity, quality of life, and treatment outcome in patients with fibromyalgia. (2nd January 2016) - Jiao, J; Davis III, JM; Cha, SS; Luedtke, CA; Vincent, A; Oh, TH
Abstract : Objectives : To evaluate the frequency of rheumatic diseases and their association with symptom severity, quality of life (QoL), and treatment outcome in patients with fibromyalgia (FM). Method : Our study contained 536 FM patients who completed a brief, interdisciplinary fibromyalgia treatment programme (FTP) at our institution, with emphasis on cognitive behavioural therapy (CBT). The Fibromyalgia Impact Questionnaire (FIQ) and the 36-item Short Form Health Status Questionnaire (SF-36) were completed at initial evaluation and at 6 and 12 months after the FTP. The presence of inflammatory rheumatic disease (IRD) was determined by physician diagnoses. A two-sample t-test and multivariate linear regression analyses were performed to compare the rheumatic and non-rheumatic groups. Results : Thirty-six patients (6.7%) had documented IRD. At baseline, the rheumatic group had poorer scores in SF-36 physical functioning (p = 0.02), pain index (p = 0.01), and physical component summary (p = 0.009) than the non-rheumatic group. After treatment, both groups tended to improve; however, the rheumatic group had significantly less improvement on the FIQ subscales in pain (p = 0.01) and missed work days (p = 0.01), as well as in the SF-36 physical functioning (p = 0.01), pain index (p = 0.049), and physical component summary (p = 0.049) compared with the non-rheumatic group. Conclusions : The frequency of rheumatic diseases in patients with FM seen at FTP was 6.7%. FM patients with rheumatic diseases were found to have worse SF-36-assessed pain and physical health and less improvement in these measures following treatment from FTP than patients without rheumatic diseases. FM patients with rheumatic disease may require additional intervention to address underlying rheumatic disease-related limitations.